The use of high impact practices (HIPs) on chemistry lesson design and implementation by pre-service teachers - Suthida Chamrat (2018)
© 2018 Author(s). The quality of lesson design is essential to learning effectiveness. Research shows some characteristics of lessons have strong effect on learning which were grouped into "High Impact Practices or HIPs. This research aims to examine the use of HIPs on chemistry lesson design as a part of Teaching Science Strand in Chemistry Concepts course. At the first round of lesson design and implementing in classroom, 14 chemistry pre-services teachers freely selected topics, designed and implemented on their own ideas. The lessons have been reflected by instructors and their peers. High Impact Practices were overtly used as the conceptual framework along with the After-Action Review and Reflection (AARR). The selected High Impact practice in this study consisted of 6 elements: well-designed lesson, vary cognitive demand/academic challenge, students center approach, opportunity of students to reflect by discussion or writing, the assignment of project based learning or task, and the lesson reflects pre-service teachers' Technological Pedagogical Content Knowledge (TPACK). The second round, pre-service teachers were encouraged to explicitly used 6 High Impact Practices in cooperated with literature review specified on focused concepts for bettering designed and implemented lessons. The data were collected from 28 lesson plans and 28 classroom observations to compare and discuss between the first and second lesson and implementation. The results indicated that High Impact Practices effect on the quality of delivered lesson. However, there are some elements that vary on changes which were detailed and discussed in this research article.